Мермитиды (Nematoda, Mermithidae) — паразиты стрекоз западных областей УССР - Рубцов, И.А.; Павлюк, Р.С. (Вестник зоологии, 1972)
Dragon-flies were analysed for infestation with parasites in 1966—1969 in the Lvov and Volyn regions. About 10400 adult dragon-flies and 200 larvae of different species were dissected. In the course of dissections more than 20 individuals of mermithides were found. All of them proved to be new for science and are described under the names: Hexamermis (?) pachydermis sp. n., Agamomermis coenagrionis sp. n., Agamomermis lestis sp. ll., Paramermis zygopterorum sp. n. and Mermithidae gen. et sp. indet.
Mermithides from dragon-flies which are referred to the genera Agamomermis and Hexamermis are likely to be real representatives of peculiar new genera of the family. To solve this problem it is necessary to rear adult worms from the larvae.